Tafsir Konstitusionalitas terhadap Batas Usia Pemidanaan Anak - Hwian Christianto (Jurnal Konstitusi, 2016)
Child’s age limit acts is an absolute requirement which shall be notified in order to avoid him or her to be a victim. Acts No. 3, 1997 about     Court of Children  states  that 8 (eight) years old as the limit and it can   be proposed to. Of course this statement brings consequence to children growth’s rights and it is considered as a threat that he/she shall experience an hard law-process. On another hand, the decision of Supreme Court No. 1/PUU-VII/2010 answers this problem, by pulling up the application and deciding 12 years old as a new limit for the accused child. The regulation definitely brings a big change into child’s criminal law concept in Acts No. 3, 1997. The objection of law’s  application as limitation for a child    in the court also said by the applicant and considered as legality and human right trafficking.